Carbon nitride used as a reactive template to prepare mesoporous molybdenum sulfide and nitride. Issue 35 (18th June 2021) - Ryaboshapka, Daria; Afanasiev, Pavel
Abstract : Carbon nitride C3 N4 has been used as a sacrificial template to prepare inorganic materials with a hierarchical pore structure. Abstract : Carbon nitride C3 N4 has been used as a sacrificial template to prepare inorganic materials with hierarchical pore structure. C3 N4 impregnated with ammonium heptamolybdate was treated in reactive gas mixtures (H2 S/H2 or NH3 /H2 ). This approach allowed mesoporous molybdenum sulfide and molybdenum nitride materials to be obtained that replicate the morphology of the C3 N4 template. Advantageous catalytic properties have been demonstrated in the thiophene hydrodesulfurization (HDS) and electrochemical hydrogen evolution reaction (HER). The highest rates in both reactions were observed for partially sulfidized Mo2 N solid.